Does Smoking Affect Short-Term Patient-Reported Outcomes After Lumbar Decompression?. Issue 5 (June 2021) - Goyal, Dhruv K. C.; Divi, Srikanth N.; Bowles, Daniel R.; Mujica, Victor E.; Kaye, I. David; Kurd, Mark F.; Woods, Barrett I.; Radcliff, Kris E.; Rihn, Jeffrey A.; Anderson, D. Greg; Hilibrand, Alan S.; Kepler, Christopher K.; et al.
Study Design: Retrospective cohort study. Objective: The goal of this study was to determine how smoking status influences patient-reported outcome measurements (PROMs) in patients undergoing lumbar decompression surgery. Methods: Patients undergoing lumbar decompression between 1 to 3 levels at a single-center, academic hospital were retrospectively identified. Patients <18 years old, and those undergoing surgery for infection, trauma, tumor, or revision, with less than 12 months of follow-up were excluded. Patients were divided into 3 groups: (1) never smokers (NSs); (2) current smokers (CSs); and (3) former smokers (FSs). PROMs analyzed included the Physical Component Score and Mental Component Score of the Short Form-12 Health Survey, the Oswestry Disability Index, and Visual Analogue Scale Back and Leg pain scores. One-way ANOVA was used to compare preoperative and postoperative scores between smoking groups, and multiple linear regression analysis was performed to determine whether smoking status predicted change in each outcome score, controlling for factors such as age, sex, body mass index, and other clinical variables. A P value <.05 was considered to be significant. Results: A total of 195 patients were included in the final cohort, with 121 (62.1%) patients in the NS group, 22 (11.3%) in the CS group, and 52 (26.6%) in the FS group. There were no significant differences between groups at baseline or postoperatively. Smoking status was also not a significant predictor of change in any outcome scores over time on multivariate analysis. Conclusion: These results suggest that smoking status does not significantly affect short-term complications or outcomes in patients undergoing lumbar decompression surgery.